Chitosan mediated metabolite elicitation and growth responses in kasthuri turmeric(curcuma aromatica) - Nivya J Thengumpally (Department of plantation cropsmand spices, college of agriculture, 2019)
The present investigation entitled “Chitosan mediated metabolite elicitation and growth responses in kasthuri turmeric (Curcuma aromatica Salisb.)” was conducted at the Department of Plantation Crops and Spices, College of Agriculture, Vellayani during 2017-2019 with the objective to study the effect of different concentrations of chitosan on plant growth, yield and metabolite production in Curcuma aromatica. The planting material for the study was obtained from Instructional Farm, College of Agriculture, Vellayani. The experiment was laid out in completely randomized block design (CRD) with nine treatments and three replications. The treatments consisted of foliar spray with different concentrations of chitosan and control treatments viz., chitosan 0.5 g l-1 (T1), chitosan 1 g l-1 (T2), chitosan 1.5 g l-1 (T3), chitosan 2 g l-1 (T4), chitosan 2.5 g l-1 (T5), chitosan 3 g l-1 (T6), acetic acid (0.25 per cent) spray (T7), water spray (T8) and control (T9). The treatments were given at 3 and 5 months after planting (MAP). The plant growth parameters viz., plant height, number of tillers, number of leaves, leaf area and shoot weight were recorded at 4 and 6 MAP. All chitosan foliar spray treatments resulted in significantly taller plants compared to treatments devoid of chitosan at 6 MAP, with the highest value (109.91 cm) in T6. T5 and T6 recorded significantly higher number of leaves at 4 MAP while at 6 MAP, it was recorded in treatments, T2 to T6. Similar trend was observed with leaf area also. T4 to T6 recorded significantly higher shoot weight at 4 MAP and T5 to T6 at 6 MAP. The highest dry weight (42.69 g) was recorded in T5 and 63.0 g in T6 at 4 MAP and 6 MAP, respectively. Number of tillers did not show any variation among treatments at both stages of observation. The plant growth parameters viz., rhizome spread, rhizome thickness, number of fingers, root length, root spread and root weight were recorded at 4 MAP, 6 MAP and at harvest. Significant enhancement in rhizome spread was observed only at harvest, in T6, which was on par with T5. The higher concentrations of chitosan foliar spray significantly influenced rhizome thickness at 6 MAP and at harvest; significantly higher values were observed in treatments, T2 to T6 at 6 MAP and T3 to T6 at harvest. At all stages of observation, number of fingers was found to be significantly higher in T5 and T6. Root length and root spread were significantly higher with the treatments T5 and T6 at 6 MAP and at harvest. Significant variation in root weight was observed in C. aromatica only at 6 MAP. The observations on plant metabolites viz., chlorophyll content, total proteins and defence enzymes were recorded at 4 and 6 MAP. T4, T5 and T6 were observed to have significantly higher chlorophyll content among the treatments, at 6 MAP. Total proteins and defense enzymes were observed to give significant variation at both stages of observation. Protein content was found to be significantly higher (6.89 mg g-1) in T5 at 4 MAP and in treatments T4 to T6 at 6 MAP, the highest value being recorded in T6 (8.46 mg g-1). Catalase and peroxidase activity were found significantly higher in T5 and T6 at both stages of observation. SOD activity was found to be significantly higher in T6 at 4 MAP and T4 to T6 at 6 MAP. The observations on curcumin content, volatile oil, oleoresin and carbohydrate content were recorded at harvest. Curcumin, volatile oil and oleoresin was observed to be significantly higher in treatments T4, T5 and T6. T5 and T6 recorded significantly higher carbohydrate content among the various treatments tried. The physiological parameters viz., leaf area index (LAI), stomatal conductance, photosynthetic rate, proline content and cell membrane integrity (CMI) were recorded at 4 and 6 MAP. LAI was found to be significantly higher in treatments T5 and T6 at 4 MAP and T2 to T6 at 6 MAP. With respect to stomatal conductance, T4, T5 and T6 gave significantly higher values at both, 4 and 6 MAP. T6 recorded significantly higher photosynthetic rate among the treatments tried at both stages of observation. All foliar spray treatments with chitosan recorded significantly higher proline content at 4 MAP and T4 to T6 at 6 MAP. CMI was found to be significantly superior in T3 to T6 at 4 MAP, but did not show any variation at 6 MAP. The dry matter production was recorded at 4 MAP, 6 MAP and at harvest. The highest dry matter production was obtained in T6 at all stages of observation and was comparable with T5. The foliar spray treatments did not show any significant variation with respect to net assimilation rate during the period between 4 and 6 MAP. The chitosan foliar spray significantly influenced the rhizome yield, crop duration and harvest index of C. aromatica. T5 (170.95 g plant-1) and T6 (173.27 g plant-1) were found significantly superior to all other treatments with regard to rhizome yield. Crop duration and harvest index of plants exposed to chitosan foliar spray were found to be significantly superior to those devoid of chitosan. Uptake of major plant nutrients (N, P and K) were found to be maximum in T5 and T6. In the present study, chitosan application at different concentrations as foliar spray at 3 and 5 MAP elicited plant growth, production of curcumin, volatile oil, oleoresin and yield. The chitosan concentration of 2.5 and 3 g l-1 gave maximum enhancement in the yield and metabolite production.